1983
DOI: 10.1159/000241730
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Increase in the Metabolism of Leucine and Valine

Abstract: The catabolism of tritium-labeled leucine, valine, and glycine was determined by measuring the appearance of tritium-labeled water at various postnatal and adult ages in rats. Results for leucine and valine show a marked increase in the formation of labeled water during the 3rd postnatal week. The partial exclusion of leucine and valine from brain, as a result of the blood-brain barrier, particularly enhances observation of labeled water formation in that the product (water) and precursor (amino acid) are larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
1988
1988

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Fuller et al [17] estimated the oxidation of leucine in the brain and liver of rats by mea suring the production of 3H20 from injected 3H-leucine. They found that oxidation in creased abruptly after 15 days of age.…”
Section: Discussionmentioning
confidence: 99%
“…Fuller et al [17] estimated the oxidation of leucine in the brain and liver of rats by mea suring the production of 3H20 from injected 3H-leucine. They found that oxidation in creased abruptly after 15 days of age.…”
Section: Discussionmentioning
confidence: 99%